PENGARUH PERTUMBUHAN EKONOMI INVESTASI, UPAH MINIMUM PROVINSI TERHADAP PENYERAHAN TENAGA KERJA DI SULAWESI SELATAN - Kurnia Tahir (Jurnal Ekonomi Bisnis Syariah, 2018)
The purpose of this study was to determine the economic growth, investment and wages minimum level of employment in the Province of South Sulawesi period 2002-2017. The process of analysis data is in the form of analysis multiple regression. sources Data used are secondary data in the form of official publications about data economic growth, investment, and provincial minimum wages obtained from the Central Statistics Agency of South Sulawesi. The results showed that (1) economic growth had a positive and significant effect on employment (2) investment had a positive and insignificant effect on employment (3) the provincial minimum wage had a positive and significant effect on employment in Province of South Sulawesi.